Boost Your Body: Self-Improvement Magazine Messages Increase Body Satisfaction in Young Adults. Issue 2 (1st February 2017) - Veldhuis, Jolanda; Konijn, Elly A.; Knobloch-Westerwick, Silvia
ABSTRACT: The verbal messages that contextualize exposure to idealized body imagery may moderate media users' body satisfaction. Such contextualizing verbal messages often take the form of social comparison motives in fashion magazines, while body dissatisfaction is an important mechanism underlying various body image–related health issues like depression and unbalanced weight status. Hence, the present study applied social comparison motives as induced through magazine cover messages. Hypotheses were tested in an experimental design with social comparison motives (self-improvement vs. self-evaluation vs. control) and recipient gender as between-subjects factors and body satisfaction as within-subjects factor ( N  = 150). Results showed that self-improvement messages accompanying ideal body media models increased body satisfaction, compared to control messages and baseline measures. In contrast, the self-evaluation messages did not impact body satisfaction. Results imply that inconsistencies regarding effects from exposure to idealized body imagery are explained by the context in which media images are portrayed, evoking differential social comparison motives. Moreover, the findings imply that health communication interventions can use verbal messages on body improvement as helpful tools, if they draw on social comparison motives effectively.